Robot-Assisted Total Hip Arthroplasty Demonstrates Improved 90-Day Clinical and Patient-Reported Outcomes - Alana Prinos, BS; Weston Buehring, MHS, BS; Catherine Di Gangi, BS; Patrick Meere, MD; Morteza Meftah, MD; Matthew Hepinstall, MD (Arthroplasty Today, 2024)
Background: The utilization of technology, including robotics and computer navigation, in total hip arthroplasty (THA) has been steadily increasing; however, conflicting data exists regarding its effect on short-term clinical and patient-reported outcomes. Therefore, this study sought to explore the association between different surgical technologies and postoperative outcomes following THA. Methods: We retrospectively reviewed 9892 primary THA cases performed by 62 surgeons from a single institution from September 2017 to November 2022. Three cohorts were created based on the utilization of technology: conventional (no technology), navigation, or robotics. Patient demographics, clinical outcomes, and patient-reported outcome measures were collected over the first 90 days following surgery. This data was compared using analysis of variance and multivariate logistic regressions. In total, 4275 conventional, 4510 navigation, and 1107 robotic cases were included in our analyses. Results: The robotic cohort achieved a perfect Activity Measure for Post-Acute Care (AM-PAC) score earliest (0.1 days, P < .001). After adjusting for potential confounding variables, use of robotic assistance was associated with greater odds of achieving a perfect AM-PAC score on postoperative day 0 (odds ratio 1.6, P < .001) and greater odds of having length of stay shorter than 24 hours (odds ratio 2.3, P < .001) compared to no technology use in THA. Hip dysfunction and Osteoarthritis Outcome Score, Joint Replacement and Patient-Reported Outcomes Measurement Information System Pain Interference scores showed the greatest improvement in the robotic cohort at both 6 weeks and 3 months following surgery. Conclusions: The present study demonstrates favorable clinical and patient-reported outcomes in the first 90 days following surgery for patients undergoing robot-assisted THA compared to conventional and navigation-assisted THA.